Litigation and Settlement : New Evidence from Labor Courts in Mexico - Kaplan, David S.; Sadka, Joyce; Silva-Mendez, Jorge Luis (World Bank, Washington, DC, 2012)
Using a newly assembled data set on procedures filed in Mexican labor tribunals, the authors of this paper study the determinants of final awards to workers. On average, workers recover less than 30 percent of their claim. The strongest result is that workers receive higher percentages of their claims in settlements than in trial judgments. It is also found that cases with multiple claimants against a single firm are less likely to be settled, which partially explains why workers involved in these procedures receive lower percentages of their claims. Finally, the authors find evidence that a worker who exaggerates his or her claim is less likely to settle.